Melatonin in the dermal film limits the blood lymphocyte death in experimental thermal trauma - M. V. Osikov; E. V. Simonyan; A. A. Ageeva; Yu. I. Ageev (Медицинская иммунология, 2021)
According to WHO data, about 11 million people need medical care after burns every year. In the overall structure of burns, the share of thermal trauma (TT) is 80%. Lymphocytopenia in TT is a risk factor for infectious complications and limited repair, and the development of new tools for TT therapy using dermal films is demanded in combustiology. The aim of the study was to evaluate changes in blood lymphocyte parameters, i.e., quantitative composition and their death during experimental thermal damage under the influence of the originally developed dermal film with melatonin (MT) in 49 inbred rats. The grade IIIA TT of 3.5% body surface was modeled by contact with boiling water for 12 s. Dermal films based on sodium carboxymethylcellulose supplemented with MT at a concentration of 0.005 g/g were applied daily for 5 days. The total numbers of lymphocytes, CD45RA+ and CD3+ cells, counts of lymphocytes with signs of partial necrosis, early and late apoptosis were assessed in blood. Relative decrease in the area and rate of the burn wound epithelization were also calculated. In animals with TT, the number of blood lymphocytes decreased on days 5, 10 and 20, including CD45RA+ and CD3+, along with increased amounts of lymphocytes with signs of necrosis, late and early apoptosis. By the term of 20 days, the burn wound area was reduced by 11.5%. Usage of dermal films with MT increased the amount of CD3+ cells in blood on days 5 and 10, CD45RA+ on days 5, 10 and 20, being associated with decreased number of lymphocytes showing signs of early apoptosis on days 5, 10 and 20, as well as features of necrosis and late apoptosis on days 5 following TT, accelerates the healing of a burn wound on days 5, 10 and 20 after TT. with a 20 cent reduction of its area by the day 20. Epithelization rate of the burn wound when applying MT-supplemented dermal film on days 5, 10 and 20 increases, along with higher amounts of CD3+ in the blood, and reduced counts of lymphocytes with signs of early apoptosis.